Differences between the influence of squat jump performance and lower body isometric muscle force in the function of the swimming start performance efficiency - Durovic, M.; Dopsaj, M.; Madic, D.; Bojic, I.; Okicic, T. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Aim of this research was to determine the differences between the influence of squat jump (SJ) performance and standing knee extensors isometric muscle force (KE) in the function of the swimming start performance efficiency. Forty-six trained swimmers preformed 3x10m kick-start. The best 10m trial (t10m) was selected for each swimmer. K-Means Cluster Analysis was used to divide swimmers into three groups based on the effectively performed start trial, i.e. by using values of t10m. First group (AAG) included swimmers whose mean values of t10m are above average (t10m=3.69 ± 0.13s; n=9), second group (AG) with average mean values of t10m (t10m=4.00 ± 0.09s; n=23) and third group (BAG) with mean values of t10m below average (t10m=4.34 ± 0.14s; n=14). Regression model (OMR) was used to predict the t10m including SJ and KE performance. Results showed that the OMR for AAG was defined using following variables: SJ maximum height and maximal relative power (SJ_h and SJ_Pmax), along with the isometric muscle force of the knee extensors in absolute and relative values (KE_Fmax and KE_FmaxRel), and relative specific explosive isometric muscle force of the knee extensors (KE_RFD50%Rel). The OMR for AG was defined only by SJ_h, for BAG there was no OMR model used to predict the t10m. Differences in the influence of SJ and KE performance in the function of the swimming start performance efficiency are represented by: SJ_Pmax, KE_Fmax, KE_FmaxRel and KE_RFD50%Rel. It can be concluded that the swimmers who possess better developed aforementioned contractile abilities have higher physical potential for performing a faster start.